The State, Business And Society At The Crossroads Of The Circular Economy: Armenia’s Main Challenges And Prospects - Manucharyan, Meri (ՀՀ ԳԱԱ ՏԻ)
The transition toward circular economy is becoming strategically important for Armenia, as the country’s economic and environmental systems continue to operate within a predominantly linear resource-use model. This study examines Armenia’s progress toward circularity by analyzing the interaction between the state, business, and society, while identifying key structural, institutional, and behavioral barriers. The research methodology is based on comparative and descriptive analysis, using international statistical data, national sources, and government policy documents. The aim of the study is to analyze the direction of the circular economy in Armenia, assessing the current state of the country, key challenges and opportunities, as well as the interaction between the state, business and society during this process. To achieve the study’s goal, the following tasks were set: to present the main indicators of Armenia, compare them with international standards, identify policy and institutional constraints, assess stakeholder participation and formulate context-specific recommendations tailored to the needs of Armenia. The results show that Armenia is at the initial stage of forming a circular economy: characterized by a low level of waste recycling, limited use of Extended Producer Responsibility, lack of a monitoring system and weak public engagement. At the same time, international experience indicates significant unrealized potential in terms of efficient use of resources and increasing the resilience of the economy. The transition to a circular economy in Armenia requires data-based policies, modernization of infrastructure, application of economic incentives and strengthening state-business society cooperation.
Keywords: Macroeconomics